2015
DOI: 10.1083/jcb.201405099
|View full text |Cite
|
Sign up to set email alerts
|

Dense fibrillar collagen is a potent inducer of invadopodia via a specific signaling network

Abstract: High-density fibrillar collagen matrix induces invadopodia formation in both fibroblasts and carcinoma cell lines through a kindlin2-dependent mechanism that drives local ECM remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 94 publications
(109 reference statements)
3
106
2
Order By: Relevance
“…This implies that it is the tugging force that is responsible for the maturation of invadopodia and not the stiffness of the matrix. Furthermore, other studies performed in 2D cultures have shown that increasing collagen matrix stiffness results in an increase in the number of invadopodia (Alexander et al, 2008;Artym et al, 2015;Das et al, 2013). While our study has found that the number of invadopodia is unaffected by tugging forces, the length is, however, clearly affected.…”
Section: Discussioncontrasting
confidence: 71%
“…This implies that it is the tugging force that is responsible for the maturation of invadopodia and not the stiffness of the matrix. Furthermore, other studies performed in 2D cultures have shown that increasing collagen matrix stiffness results in an increase in the number of invadopodia (Alexander et al, 2008;Artym et al, 2015;Das et al, 2013). While our study has found that the number of invadopodia is unaffected by tugging forces, the length is, however, clearly affected.…”
Section: Discussioncontrasting
confidence: 71%
“…Furthermore, cells react differently to the substrate depending on its stiffness (Collin et al, 2006;Juin et al, 2012;Labernadie et al, 2014). For instance, a recent study has demonstrated that cells from the metastatic breast cancer line MDA-MB 231 preferentially form integrin-dependent actin dots on a high density of fibrillar collagen, which corresponds to compressed and fixed collagen I (Artym et al, 2015). Several other studies have demonstrated that cells preferentially form linear actin structures on fibrillar collagen I (Monteiro et al, 2013;Schachtner et al, 2013).…”
Section: Invadosome Plasticitymentioning
confidence: 99%
“…However, similar to focal adhesions, invadosomes connect cells with the ECM through contact foci consisting of large multiprotein complexes. Thus, owing to the dynamic nature of this complex, identifying the full molecular identity of these structures is challenging (Artym et al, 2015;Beaty et al, 2013;Sharma et al, 2013;Valenzuela-Iglesias et al, 2015). Currently, there is no study that is able to define the invadosome proteome as accurately as has been done for focal adhesions (Goicoechea et al, 2014;Robertson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1, A). 8 Interestingly, the induction of abundant invadopodia by HDFC was found to be independent of growth factor stimulation. 8 Moreover, HDFC not only stimulated invadopodia formation in transformed cancer cells, but also elicited high numbers of functional invadopodia in normal human fibroblasts.…”
mentioning
confidence: 99%
“…8 We have also developed an in vitro high-density fibrillary collagen (HDFC) matrix consisting of a densely packed network of fibrillar collagen type I compacted by centrifugation to closely mimic desmoplastic collagen. 8 Direct comparisons of invadopodial response to a variety of ECMs revealed that dense fibrillar collagen is a superior inducer of invadopodia in a variety of tumor cell lines ( Fig. 1, A).…”
mentioning
confidence: 99%